2011
DOI: 10.1074/jbc.m110.163246
|View full text |Cite
|
Sign up to set email alerts
|

Charge Transport in the ClC-type Chloride-Proton Anti-porter from Escherichia coli

Abstract: The first chloride transporter identified in the superfamily of ClC chloride channels was from Escherichia coli (EClC) (Accardi, A., and Miller, C. (2004) Nature 427, 803-807). Pathways, energetics, and mechanism of proton and chloride translocation and their coupling are up to now unclear. To bridge the hydrophobic gap of proton transport, we modeled four stable buried waters into both subunits of the WT EClC structure. Together they form a "water wire" connecting Glu-203 with the chloride at the central site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 51 publications
(102 reference statements)
0
28
0
Order By: Relevance
“…To determine an initial protonation pattern in CcO, we evaluated all pK A values by electrostatic energy computations using karlsberg+ 37,38 for the CcO crystal structure (PDB: 2GSM 11 ) as done in previous applications 36,39 . The resulting protonation pattern was applied for all MD runs, if not stated otherwise.…”
Section: Computing Electrostatic Energies Of Protonation Pattern Watmentioning
confidence: 99%
“…To determine an initial protonation pattern in CcO, we evaluated all pK A values by electrostatic energy computations using karlsberg+ 37,38 for the CcO crystal structure (PDB: 2GSM 11 ) as done in previous applications 36,39 . The resulting protonation pattern was applied for all MD runs, if not stated otherwise.…”
Section: Computing Electrostatic Energies Of Protonation Pattern Watmentioning
confidence: 99%
“…Neutralization of either glutamate eliminates H + translocation by ClC-ec1 (9, 28). However, the discovery of these H + binding sites also raised a mechanistic puzzle (3, 23): How do protons translocate between the two sites, which are separated by a ∼15-Å-long, largely hydrophobic region within the lumen of the protein?Since the report of its first crystal structure, a large number of computational studies have aimed at investigating various molecular details related to the CLC H + transport mechanism (27,(29)(30)(31)(32)(33)(34). One model emerging from these studies proposes that water molecules may connect the two H + sites (Glu ex and Glu in ) and, thereby, facilitate H + transport (29,30,34).…”
mentioning
confidence: 99%
“…Despite the differences in the functions between the two types of CIC proteins, all members of this superfamily contain double-barreled architecture and possess voltage-dependent gating mechanism (Maduke et al 2000). EriC is a homodimeric transmembrane protein and exchanges protons with chlorides in a fixed 2:1 stoichiometry (Kieseritzky and Knapp 2010). Results from protein BLAST with L. reuteri 6475 EriC sequence revealed that proteins with EriC functional domains are ubiquitously present in bacteria including those that are members of the human intestinal microbiome.…”
Section: Discussionmentioning
confidence: 99%